Use of wiris quizzes in an online calculus course - Remei Calm; Ramon Masià; Carme Olivé; Núria Parés Mariné; Francesc Pozo; Jordi Ripoll; Teresa Sancho-Vinuesa (OmniaScience, 2017)
Calculus courses often present a large number of difficulties to undergraduate students of scientific studies, especially in engineering degrees. These difficulties are sometimes related to teaching and assessment strategies. In this paper, a teaching innovation experience is presented within the framework of the Universitat Oberta de Catalunya. This teaching experience is focused on a continuous assessment through a systematic use of the so-called WIRIS quizzes. Academic outcomes are very positive from both quantitative and qualitative viewpoints.